Modeling wildland fire propagation using a semi-physical network model. (October 2015) - Adou, J.K.; Brou, A.D.V.; Porterie, B.
Highlights: Wildland fire spread is modeled using a fast and simple semi-physical network model. Model results are compared with data from laboratory-scale and prescribed burning experiments. Hierarchy of model parameters is established by means of a sensitivity analysis. Abstract: In this paper we present a surface wildfire model which can be used to develop and test new firefighting strategies and land use planning practices. This model is simple, easy to implement and can predict the rate of fire spread, the fire contour and both burning and burned areas. It also incorporates weather conditions and land topography. The predictive capability of the model is partially assessed by comparison with data from laboratory-scale and prescribed burning experiments. A sensitivity analysis is conducted to identify the most influential input model parameters controlling fire propagation.